An empirical study into the effects of state ownership and board characteristics on earnings management: the Chinese context - Li, Qinlin (2020)
This paper assesses the impacts of state ownership and board characteristics on earnings management practices among Chinese listed firms over the period from 2015 to 2019. Notwithstanding there exists a host of literature in corporate governance, the understanding of state ownership and Chinese earnings management practices remains unclear. Therefore, this paper explores if there are distinctions in earnings management between state-owned enterprises (SOEs) and non-state-owned enterprises (NSOEs) as privatization moves forward and which board characteristics can constrain earnings management. The level of earnings management is represented by discretionary accruals and board size, board diligence, board independence as well as CEO duality are regarded as board characteristics. The study applies the quantitative research methodology based on secondary financial and corporate governance data collected from the CSMAR database. The ultimate results demonstrate that there is no distinction between state-owned enterprises and non-state-owned enterprises from 2015 to 2019. What is more, both board size and CEO duality are negatively associated with earnings management practices. Board diligence has a positive association with earnings management. However, no significant relationship has been investigated between board independence and earnings management. The findings of this paper can provide crucial implications for stakeholders and regulators. Moreover, it helps potential global investors to gain an understanding of earnings management practices in China. Key words: earnings management; state ownership; board characteristics